Poststroke Cognitive Impairment Research Progress on Application of Brain-Computer Interface. (7th February 2022) - Sun, Xiaowei; Li, Mingyue; Li, Quan; Yin, Hongna; Jiang, Xicheng; Li, Hongtao; Sun, Zhongren; Yang, Tiansong
Abstract : Brain-computer interfaces (BCIs), a new type of rehabilitation technology, pick up nerve cell signals, identify and classify their activities, and convert them into computer-recognized instructions. This technique has been widely used in the rehabilitation of stroke patients in recent years and appears to promote motor function recovery after stroke. At present, the application of BCI in poststroke cognitive impairment is increasing, which is a common complication that also affects the rehabilitation process. This paper reviews the promise and potential drawbacks of using BCI to treat poststroke cognitive impairment, providing a solid theoretical basis for the application of BCI in this area.